2020
DOI: 10.1021/acsami.0c02273
|View full text |Cite
|
Sign up to set email alerts
|

Methane Utilization to Methanol by a Hybrid Zeolite@Metal–Organic Framework

Abstract: The development of an effective approach for methane utilization, especially methane conversion to methanol, is a crucial challenge that has remained unsolved satisfactorily. Herein, we propose an alternative concept of methane utilization to methanol over Fe-ZSM-5@ZIF-8. The concept is to use the designed composite as a dual catalyst in which ZIF-8 and Fe-ZSM-5 act simultaneously as a gas adsorbent and catalyst, respectively. In this case, methane can be adsorbed on ZIF-8 at 50 °C and subsequently converted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…Room temperature has been also successfully checked with the help of photocatalysis (An et al, 2022). 4) MOF can catalyst the reaction without NP, which is an unexpected result that needs further research (Imyen et al, 2020). Apart from the obvious role of MOF as a support of NP to anchor the active site and to permit the diffusion of reactants and products, the conclusion is that a control with only MOF is necessary.…”
Section: Methane To Methanolmentioning
confidence: 94%
“…Room temperature has been also successfully checked with the help of photocatalysis (An et al, 2022). 4) MOF can catalyst the reaction without NP, which is an unexpected result that needs further research (Imyen et al, 2020). Apart from the obvious role of MOF as a support of NP to anchor the active site and to permit the diffusion of reactants and products, the conclusion is that a control with only MOF is necessary.…”
Section: Methane To Methanolmentioning
confidence: 94%
“…Methane is set to become the most abundant hydrocarbon feedstock for the synthesis of petrochemical derivatives, with the depletion of oil reserves . Consequently, the chemical conversion of methane to value-added chemicals is attracting increasing interests. , Currently, the dominant method of methane upgradation is the indirect conversion of methane to hydrocarbons/oxygenates via formation of syngas (H 2 + CO) by steam reforming, CO 2 reforming, or partial oxidation, followed by Fisher–Tropsch synthesis. , Direct methane conversion to light hydrocarbons by oxidative and nonoxidative coupling of methane provides prospects for more efficient and one-step methane upgradation by circumventing the energy-intensive syngas production step. , Nonoxidative coupling of methane (NCM) is preferable due to its unique capability of generating C 2+ hydrocarbons and H 2 from methane without the unselective production of undesirable CO x …”
Section: Introductionmentioning
confidence: 99%
“…This overcomes the shortcomings of conventional catalysts, such as (1) short life span due to coking, (2) low surface area-active sites for enhancing the carbonization reaction, and (3) nonhomogeneous dispersion of metal sites. 31 , 32 The first study that reported on the incorporation of MOF into Ni-based catalysts for the DRM process can be dated back to 2019 in the study by Chin et al 33 They had prepared a bimetallic (Ni-Ce) MOF-derived catalyst in the DRM process and proved that the application of MOF as a precursor improved its catalytic performance as the MOF application had successfully produced higher-dispersed particles. It is then followed by Karam et al, 25 who have synthesized a highly porous Ni-Al/MOF MIL-53 for the DRM reaction in 2020.…”
Section: Introductionmentioning
confidence: 99%